Rekonstruksi Kurikulum Bahasa Inggris Sekolah Dasar Berbasis Communicative Language Teaching untuk Penguatan Dimensi Lulusan - Dzulqa, Eryza Tiara; Mulyasari, Effy (Institut Agama Islam Negeri Kendari, 2026)
This study examines the implementation of Communicative Language Teaching (CLT) in elementary school contexts to enhance students’ communicative competence. The study addresses the gap between theoretical assumptions of CLT and its practical application in classrooms, particularly within the Indonesian educational setting. The objective of this research is to analyze how CLT strategies are applied and to evaluate their impact on students’ speaking skills and classroom interaction. A qualitative research design was employed, involving classroom observations, interviews with teachers, and document analysis. The findings indicate that the use of communicative activities such as role play, group discussions, and interactive tasks significantly improves students’ confidence and ability to communicate in English. However, several challenges were identified, including limited teacher proficiency, lack of instructional resources, and constraints related to traditional teaching practices. The study concludes that CLT is an effective approach for promoting active learning and communicative competence in elementary education. Its successful implementation requires adequate teacher training and contextual adaptation. These findings contribute to the development of more effective language teaching practices in primary education. Keywords: communicative competence; communicative language teaching; elementary education; speaking skills